Fenomena Konten Challenge Viral di Youtube Pada Kalangan Mahasiswa KPI 5C: Studi Kasus Konten Challenge Pada Kanal Youtube @Mrbeast - Hayyan, Nabil; Iffah, Ismina; Uli S., Akhmad; F.N., Daffa Atha; Nisa, Pia Khoirotun (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of digital technology has had a major impact on the way humans interact and consume information. One of the media that has a strong influence in disseminating information and global trends is YouTube. YouTube not only functions as an entertainment platform, but also as a space for users to learn, express and participate in social phenomena. Among teenagers, YouTube has become one of the main platforms for consuming popular content, with trends often being adopted and imitated en masse. Challenge video content is a form of trend that often spreads widely among users, especially through the influence of well-known content creators. In this research, researchers used an interpretive paradigm. The interpretive paradigm is a methodological approach in social research that emphasizes the subjective understanding of individuals and how they give meaning to their experiences in a particular social context. Based on the results of research conducted and the results of our interviews, it shows that the challenge phenomenon is viral among KPI 5C students, which was inspired by content on the YouTube channel Mr. Beast, is a clear example of Social Imitation Theory (Social Learning Theory). In this context, students not only imitate the pattern of challenges that provide entertainment and great prizes but also adopt creativity and innovation in their own content creation.